2019
DOI: 10.3390/mi10120833
|View full text |Cite
|
Sign up to set email alerts
|

Automated Pre-Analytic Processing of Whole Saliva Using Magnet-Beating for Point-of-Care Protein Biomarker Analysis

Abstract: Saliva offers many advantages for point-of-care (PoC) diagnostic applications due to non-invasive, easy, and cost-effective methods of collection. However, the complex matrix with its non-Newtonian behavior and high viscosity poses handling challenges. Several tedious and long pre-analytic steps, incompatible with PoC use, are required to liquefy and homogenize saliva samples before protein analysis can be performed. We apply magnet-beating to reduce hands-on time and to simplify sample preparation. A magnet i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 42 publications
0
27
0
Order By: Relevance
“…Furthermore, novel biodetection systems via protein fingerprinting with data processing were proposed as a convenient system for the examination of periodontal disease (27). Methods, which reduce hands-on time and easy sample preparation, like magnet-beating were shown to be suitable for preanalytic processing of saliva for automated point of care (PoC) protein analysis (28). Those PoC devices can be based on various techniques for the detection of periodontopathogens, proteins, metabolites, and small molecules (29,30).…”
Section: Diagnostic Methodsmentioning
confidence: 99%
“…Furthermore, novel biodetection systems via protein fingerprinting with data processing were proposed as a convenient system for the examination of periodontal disease (27). Methods, which reduce hands-on time and easy sample preparation, like magnet-beating were shown to be suitable for preanalytic processing of saliva for automated point of care (PoC) protein analysis (28). Those PoC devices can be based on various techniques for the detection of periodontopathogens, proteins, metabolites, and small molecules (29,30).…”
Section: Diagnostic Methodsmentioning
confidence: 99%
“…Results are in line with past work on assay development by the co-authors Mavridis et al [34], who have shown that the crude lysis-direct amplification option performed very closely to a typical magnetic bead-based bind-wash-elute extraction and purification followed by PCR (comparison performed by means of the resulting Ct values). Furthermore, previous work on microfluidic integration by the authors has demonstrated the possibility of homogenizing biological matrices (e.g., human saliva [49], bacteria [50], cells [51], swabs [52]) using disk-integrated magnets that are actuated by external (still on LabDisk Player) magnets [53]. Therefore, upon suitable adaptation of the VectorDisk microfluidic design, the lysis and homogenization of mosquito pools could be translated from an ex situ manual (currently) process to an in situ automated (on disk) process, and be followed by in situ dilution and amplification towards a truly fully-automated vector-to-result analysis.…”
Section: The Vector Study Resultsmentioning
confidence: 99%
“…The potential utility of these modified Cross equations is in determining a way to rapidly shear saliva samples using a simple microfluidic device or mixer, rather than subjecting the saliva to freezing or flowing the saliva through a longer tube to simulate the cumulative shear thinning shown in Figure 2. The shear rate experienced in the Cannon Fenske viscometer used for these experiments is on the order of 2 s À1 , so based on the Figure 2 data of approximately a total time of 80 seconds of shearing is needed in order to reach a stable and minimum kinematic viscosity a device capable of deliver a shear rate of 200 s À1 which is well within the reach of portable and low cost homogenizers [16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%